Karakterisasi Kandungan Protein Berbagai aksesi Koro Lokal sebagai Upaya Penggalian Sumber Pangan Fungsional - Elly Purwanti; Wahyu Prihanta; Tutut Indria Permana (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
There are some local beans which were was known by Indonesian people, namely Dolichos lablabL. and PhaseoluslunatusL. This group of legume have high protein content which can be used as alternative sources of protein. This study aimed to determine the protein content of various local bean accessions of D. lablab and P. lunatuswhich collect fromMalang, Madura, Nusa Tenggara Barat, andProbolinggo. Protein analysiswas performed using AOAC 2005. The data was analysis using One-Way ANOVA. The result showed that local bean from Madura region had the highest protein content. One-Way ANOVA analysis showed that there were differences in protein levels of D. lablaband P. lunatusin each region.